Engineering employability skill development framework using university-industry collaboration: Service-dominant logic perspective - Nurul Aqila, Hasbullah (2021)
Engineers are often regarded as one of the most crucial professions in a country. To produce future engineers, the university plays a vital role as one of the major key stakeholders in developing and providing appropriate engineering employability skills among engineering students. The current unemployment situation has in fact increased competition among engineering graduates, therefore, universities need to strengthen the collaboration with industry players to promote a mutual goal in enhancing employability skills among engineering students. In this research, Service-Dominant Logic, or also known as S-D logic is used as the fundamental applied as service value co-creation between university and industry as two stakeholders in improving employability skills. This research employed a qualitative research using case study method. The method of data collection used were interviews which were divided into three cases known as Case A, Case B and Case C, where all cases have included both university and industry stakeholders. A framework is developed based on three key elements of S-D logic in value co-creation of University-Industry Collaboration (UIC) that are recognized as resources, interactions and values. The element of resources is divided into two sub-elements identified as operant and operand resources. There are four items based on operant resources: engineering employability skills, communication skills, interpersonal skills and problem solving. There are three items in operand resources, categorized as laboratory, funding and industry-based modules. The elements of interactions are divided into three sub-elements: education and training, services and consulting, and research activities. In the values element, there are two sub-elements that determine the value that can benefit both as an individual and as an organization. For individuals, graduates can benefit from graduate employability. Meanwhile, for organizations, universities and industries can benefit by sharing their expertise, knowledge and resources. For future research, the involvement of graduates with both stakeholders are recommended to expand the findings framework.